Research methods for sport management - Skinner, James (Foundations of sport management, 2014)
"Research methods courses have become a compulsory component of most degree programs in sport management. This is the first introductory research methods textbook to focus exclusively on sport management. Through the use of examples, cases and data taken from the real world of sport management it opens up a traditionally dry area of study, helping the student to understand the vital importance of sound methodology in their studies and subsequent professional practice. The book covers the full range of quantitative and qualitative methods across the whole span of the research process, from research design and the literature review to data analysis and report writing. Every chapter contains a range of useful features to aid student learning, including summaries, discussion questions and guides to further resources, as well as examples drawn from contemporary sport around the world. Research Methods for Sport Management is an essential course text for all sport management students and an invaluable reference for any sport management professional involved in operational research"--